Synthesis of LiBOB Fine Powder to Increase Solubility - Wigayati, Etty Marti; Lestariningsih, Titik; Ratri, Christin Rina; Purawiardi, Ibrahim; Prihandoko, Bambang (Makara Journal of Technology, 2017)
Lithium bis (oxalate) borate or LiBOB compound has captured interest of researchers, because it is potentially viable to be used as electrolyte salt in lithium-ion battery system. This compound is easy to synthesize and considered to be more environmentally friendly compared to conventional electrolyte salt because LiBOB does not contain halogen element. This research focused on the synthesis of LiBOB fine powder, which main purpose is improving LiBOB salt solubility in liquid electrolyte solution. This will aid the ion transfer between electrodes which in turn will increase the electrolyte performance. Solid state reaction was employed in this experiment. Synthesis of LiBOB compound was performed by reacting oxalic acid dihydrate, lithium hydroxide monohydrate, and boric acid. The resulting powder was then processed into fine powder using ball milling technique with varying milling time (0, 6, 10, and 13) hour. Microstructure of the sample was then analyzed to obtain information regarding phase formation, functional groups, grain surface morphology, surface area, pore volume, solubility, and ionic conductivity. The analysis shown that LiBOB and LiBOB hydrate phase was formed during the reaction, there was no changed in existing phase during milling process, crystallinity index was shifted to lower value but there was no difference in functional groups. Highest value in surface area was found to be 83.11 m2/g, with pore volume of 1.21311e+02 A at 10 hours milling. Smaller powder size resulted in higher solubility, unfortunately the ionic conductivity was found to be decreased.